Pengaruh Beban Kerja, Lingkungan Kerja, dan Disiplin Kerja Terhadap Produktivitas Pegawai Dinas Pertanahan dan Tata Ruang Daerah Istimewa Yogyakarta - Inayat Hanum Indriati; Aliffia Uswatun Khasanah (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The level of productivity attained in one's place of employment is critical to the accomplishment of goals set by an organisation as a whole. When working towards accomplishing the objectives of an organisation, employee productivity on the job is a critical component that must be taken into account. As a consequence of this, HRM is essential for the purpose of planning, acquiring, growing, regulating, and utilising HR in order to successfully reach good individual as well as organisational goals. The goal of this study was to determine the effect of employee workload, employee work environment, and employee work discipline partially on work productivity. The study also sought to determine the effect of employee workload, work environment, and employee work discipline simultaneously on employee productivity. A representative group of seventy staff members from the Department of Land and Spatial Planning (DIY). Collecting information by means of questionnaires and personal interviews. The methodology for the data analysis makes use of the multiple linear regression method. According to the findings of the research, employee productivity is affected in three different ways: first, by the workload; second, by the work environment; and third, by the simultaneous influence of all three factors on employee productivity. This study led to the conclusion that the work productivity of an employee will drop in proportion to the amount of work that is expected of him. On the other hand, it will grow in proportion to the quality of the work environment as well as the level of discipline that is demanded of him, and vice versa.